The Effectiveness of the Use of Image Media in Increasing Pregnant Women's Knowledge of HB-0 Immunization in Infants - Tambing, Dian (Jurnal Kebidanan Sorong, 2025)
Babies are the vulnerable groups who cannot yet be independent in meeting basic needs and making decisions, including in the inclusive group. Children's health is one of the SDG targets, namely ending infant and toddler mortality. The aim of this research is to determine the effectiveness of using image media in increasing the knowledge and attitudes of pregnant women regarding HB-0 immunization at the Kuriwamesa Community Health Center. The type of research is quasi experimental research, namely research that tests interventions on a group of subjects, with a research design using a one group pre test-post test design using the Manwednewy analysis technique. The results of the research show that the level of knowledge of pregnant women regarding giving HB-0 is valuable. Based on the results of statistical tests, it was found that the p-value results before and after treatment were 0.00, which means there is a difference, while the attitude has no value with the results of statistical tests, the p-value is 0.095. which means there is no difference, this is because there is a trigger, namely the characteristics of the mother's education with a constant p-value of 0.04, which means that education can influence a person's attitude.